Manejos de plantas de cobertura e implicações nas propriedades físicas do solo, ciclagem de nutrientes e produtividade de milho silagem - Silveira, Lucas da (2021)
One of the elements that promote the success of the no-tillage system (NTS) is the use of species with high phytomass production. The use of these results in benefits to the soil-plant system, such as natural soil decompression, increased water infiltration capacity, nutrient cycling, increased organic matter. When this system is being managed, the subsequent crop will enjoy favorable conditions to express its productive potential. The objective was to study the effect of cover species and management on the physical attributes of the soil, the levels of nutrients existing in the remaining crop residues, as well as the agronomic characteristics of the corn silage crop, grown in succession. The experiment was carried out between April 2018 and January 2020 (two agricultural years), in Marechal Cândido Rondon - PR, in Red Eutroferric Latosol, using the experimental design of strips, in a split-plot scheme, with three replications. The cover plants were placed in the plots: black oats, fodder radish, hairy vetch, black oats + fodder radish, black oats + hairy vetch and fallow. In the subplots, the management of the cover crops was allocated: chemical management (glyphosate at a dose of 1.08 kg ha-1 of acid equivalent (e.a.)) and mechanical management (grinding of plant materials with a drag crusher. It was sown in the first year in summer, the corn cultivar Coodetec 384 Powercore, in the second year, the cultivar was Morgan 30A91 Powercore, respectively in both years, 05 seeds were used per linear meter, with spacing between rows of 0.75 m. The physical characterization of the soil was performed by the volumetric ring method, trenches were opened in each subplot to collect undisturbed samples in three soil layers 0-0.1, 0.1-0.2 and 0.2-0.3 m. total porosity, macroporosity, microporosity and bulk density. The speed of decomposition and release of nutrients from crop residues of cover crops during corn cultivation in succession was evaluated. The variables analyzed were the residual amounts dry matter (DM), carbon (C), nitrogen (N), phosphorus (P) and potassium (K) contents in residual DM. In corn silage culture, the following were determined: final plant stand, plant height, ear insertion height, stem diameter and total dry matter yield. The use of cover crops and the management adopted did not influence the physical attributes of the soil during the two crop cycles. Regarding the production, decomposition and release of remaining nutrients, the use of cover crops and the maintenance of plant residues on the soil surface proved to be an advantageous practice. The highest dry matter yields and nutrient accumulation were obtained with the intercropping of black oats + fodder radish. The maize cultivated after the consortium of black oats + fodder radish showed a superior performance, being an alternative to obtain a high yield of maize silage. With the use of cover crops, nitrogen fertilization in cover crops of corn silage can be partially reduced.